2007
DOI: 10.1021/jp072548z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of OH Stretching Mode of CH3OH Chemisorbed on Ni3+ and Ni4+ by Infrared Photodissociation Spectroscopy

Abstract: Structures of nickel cluster ions adsorbed with methanol, Ni3+ (CH3OH)m (m = 1-3) and Ni4+ (CH3OH)m (m = 1-4) were investigated by using infrared photodissociation (IR-PD) spectroscopy based on a tandem-type mass spectrometer, where they were produced by passing Ni3,4+ through methanol vapor under a multiple collision condition. The IR-PD spectra were measured in the wavenumber region between 3100 and 3900 cm-1. In each IR-PD spectrum, a single peak was observed at a wavenumber lower by approximately 40 cm-1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The IRMPD spectra of the metal cluster cations, Ni þ 3 and Ni þ 4 , solvated with up to three methanol molecules were very simple with a single absorption feature. It was concluded that each methanol is on a different Ni atom and there is no methanol-methanol hydrogen bonding (Hirabayashi et al, 2007). Recent thermochemical studies of hydrated Ca 2þ ions using threshold CID (Carl, Moision, & Armentrout, 2007) concluded that six water molecules bind directly to the calcium ion closing the first solvation shell and forcing further water molecules to bind to inner shell waters.…”
Section: Solvated Metal Ionsmentioning
confidence: 99%
“…The IRMPD spectra of the metal cluster cations, Ni þ 3 and Ni þ 4 , solvated with up to three methanol molecules were very simple with a single absorption feature. It was concluded that each methanol is on a different Ni atom and there is no methanol-methanol hydrogen bonding (Hirabayashi et al, 2007). Recent thermochemical studies of hydrated Ca 2þ ions using threshold CID (Carl, Moision, & Armentrout, 2007) concluded that six water molecules bind directly to the calcium ion closing the first solvation shell and forcing further water molecules to bind to inner shell waters.…”
Section: Solvated Metal Ionsmentioning
confidence: 99%
“…Nonetheless, cleavage of these strong organic bonds is still a major challenge for any efficient chemical process and thereby continues to receive widespread attention of both academic and industrial experts alike. In fact, experimental and theoretical studies on the selective breaking of both O–H and C–H bonds of methanol have been carried out with the assistance of a wide range of compounds, such as bioinspired metal compounds, transition-metal (TM) surfaces, metal oxides, metal clusters, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[16] In contrast, the study on the reactions of pure metal clusters with methanol molecules is relatively limited. [17] In this work, we report amass spectrometric study on the reaction of cationic vanadium and cobalt clusters M n + (M = V, Co; n = 6-30) with methanol in al ow-pressure collision cell. Va nadium and cobalt were chosen for acomparative study of the early (V: [Ar]3d 3 4s 2 )a nd late (Co:[ Ar]3d 7 4s 2 )3 d transition metals.T he M n + clusters were generated via am odified Smalley type laser ablation cluster source (see experimental details in Supporting Information).…”
Section: Introductionmentioning
confidence: 99%